The causal effects of inflammatory bowel disease on its ocular manifestations: A Mendelian randomization study - Lian Luo; Xiaowei Tang; Jia Xu; Yuxi Bao; Xinyue Hu; Xiaolin Zhong (PLoS ONE, 2025)
Background Observational studies have shown that ocular manifestations of inflammatory bowel disease (IBD) are common extraintinal manifestations, among which iridocyclitis, scleritis and episcleritis are the most common. However, whether there is a causal relationship between the two is unclear. The purpose of this study was to evaluate the causality of IBD on ocular manifestations using the mendelian randomization (MR) analysis. Methods We performed a two-sample MR analysis with public genome-wide association studies (GWAS) data. Eligible instrumental variables (IVs) were selected according to the three assumptions of MR analysis. The inverse-variance weighted (IVW) method was the main method. Complementary methods included the MR-Egger regression, the Weighted Median, the Weighted Mode and MR pleiotropy residual sum and outlier (MR-PRESSO) methods. Results After false discovery rate (FDR) correction, genetically predicted IBD (IVW OR =  1.184, 95% CI: 1.125-1.247, P_FDR <  0.001), Crohn’s disease (CD, IVW OR =  1.082, 95% CI: 1.033-1.133, P_FDR =  0.007) and ulcerative colitis (UC, IVW OR =  1.192, 95% CI: 1.114-1.275, P_FDR <  0.001) were associated with an increased risk of iridocyclitis. Moreover, IBD (IVW OR =  1.128, 95% CI: 1.064-1.196, P_FDR =  0.001), CD (IVW OR =  1.077, 95% CI: 1.026-1.131, P_FDR =  0.019) and UC (IVW OR =  1.153, 95% CI: 1.069-1.243, P_FDR = 0.003) were associated with a higher risk of uveitis (uveitis includes iridocyclitis). Further sensitivity analyses validated the robustness of the above associations. However, IBD and its subtypes were not associated with scleritis, episcleritis, optic neuritis and corneal disease. Results of complementary methods were generally consistent with those of the IVW method. Conclusions Our study revealed genetically predicted associations of IBD, CD and UC on iridocyclitis and uveitis in European populations. However, IBD, CD, and UC are not causally related to scleritis, external scleritis, optic neuritis, and corneal disease.